PROGRESSIVE MODEL OF TAXATION OF MILITARY FEE: A NEW APPROACH TO FORMING UKRAINE'S TAX POLICY IN THE CONDITIONS OF POST-WAR RECONSTRUCTION - Могила, Ірина-Людмила А. (Journal of Strategic Economic Research, 2025)
The article provides a comprehensive scientific analysis of the financial and social aspects of reforming the military levy system in Ukraine, which is critically important for ensuring sustainable economic development and social justice in the post-war recovery. The study justifies the need to abandon the existing taxation model, which is fixed and does not take into account the financial status of payers, which creates an imbalance in the distribution of the tax burden. It is proposed to consider the military levy system not only as a tool for financing the defense sector, but also as an element of a socially-oriented tax policy. The main scientific novelty of the study is the development and scientific substantiation of a conceptually new model of military levy, based on the principle of progressive rate differentiation. This model involves the establishment of a flexible, progressive tax scale, where the levy rate increases in proportion to the payer's income level. Such an approach will not only significantly increase the state budget revenues necessary to finance the restoration of infrastructure, defense needs and support for veterans, but also ensure a more equitable distribution of the financial burden on society. The article proposes specific mechanisms for implementing the new system, including: development of clear criteria for determining the level of income and corresponding rates; creation of effective administrative procedures for collecting and accounting for revenues; implementation of a control system to prevent tax evasion. The proposed model is a tool that combines fiscal efficiency with social responsibility and can become the basis for the formation of a new, more balanced tax policy in Ukraine. The results of the study have significant practical value for state authorities, financial experts and scientists working on issues of financial security and economic recovery of the state. The article can also serve as a starting point for further scientific research in the field of fiscal policy.